1995
DOI: 10.1021/j100043a059
|View full text |Cite
|
Sign up to set email alerts
|

.beta.-Carboline Photosensitizers. 3. Studies on Ground and Excited State Partitioning in AOT/Water/Cyclohexane Microemulsions

Abstract: The photophysical behavior of the P-carbolines norharmane, h m a n e , and harmine has been studied in waterin-oil (w/o) microemulsions in AOT/cyclohexane. With pure solvents, solubility and partitioning studies indicate that these molecules dissolve preferentially in the organic phase but that their solubility in the aqueous phase increases upon decreasing pH as a consequence of protonation. However, in w/o microemulsions these molecules appear to be located predominantly at the surfactant/water interface. Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 7 publications
6
59
0
Order By: Relevance
“…The combined effect of the two variations induces the observed decrease of both fluorescence quantum yield and lifetime from dioxane to water. A similar increase of k nr has been observed for other compounds in dioxane-water mixtures and has been attributed to the increase of the internal conversion rate constant upon increasing water content (31)(32)(33)(34)(35).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The combined effect of the two variations induces the observed decrease of both fluorescence quantum yield and lifetime from dioxane to water. A similar increase of k nr has been observed for other compounds in dioxane-water mixtures and has been attributed to the increase of the internal conversion rate constant upon increasing water content (31)(32)(33)(34)(35).…”
Section: Resultssupporting
confidence: 77%
“…These solvent mixtures were used to represent the range of environment polarity sensed by tryptophan when the protein undergoes unfolding. Dioxane-water mixtures have been successfully used to mimic the microenvironment sensed by fluorescent probes in heterogeneous media, such as micelles (34) and micro-emulsions (35).…”
Section: Discussionmentioning
confidence: 99%
“…are by now well established as bioactive molecules. [12][13][14][15][16] The single-step synthesis of 3-acetyl-4-oxo-6,7-dihydro-12H indolo-[2,3-a] quinolizine (AODIQ) from 1-methyl-3,4-dihydro-β-carboline leads to the assumption that the molecule should have biological activity. 17 Through a series of experiments we have already established that the fluorophore molecule serves as an excellent fluorescent probe for biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…11 Electron donor-acceptor molecules capable of photoinduced intramolecular charge transfer ͑ICT͒ have been employed as reporters of microenvironments in micelles, reverse micelles, and biological membranes. 5,[12][13][14][15][16][17] The fluorophore 3-acetyl-4-oxo-6,7-dihydro-12H indolo-͓2,3-a͔ quinolizine ͑AODIQ͒ used in the present experiment has recently been shown to be an excellent probe for biological systems. 12,18 In a recent work, 19 we reported that the fluorometric behavior of AODIQ with dual emission from a locally excited ͑LE͒ state and a charge transfer ͑CT͒ state is very much dependent on the solvent polarity.…”
Section: Introductionmentioning
confidence: 99%